Entrepreneurship drain in the agricultural sector: Implications for rural development - Lee, Wen Chiat; Viswanathan, K. Kuperan; Ali, Jamal (2013)
Developing countries depend on agriculture as the basic driver for economic growth. Development projects in rural areas are often driven by government initiative to bring development to the people.However, as the economy grows and urbanization proceeds, talent moves from agriculture to other sectors such as manufacturing and services. This results in a drain in entrepreneurship talent from agriculture to the other sectors of the economy. The exit of talent and entrepreneurship from agriculture to other sectors imposes a burden on the rural sector by depriving it of entrepreneurship and thus relegating rural economies to lower growth. The resulting lack of agriculture entrepreneurship in rural areas can impede the progress of the nation. In this paper, we discuss the reasons for entrepreneurship drain in the agriculture sector as a result of rural development and the challenges development planners face in attracting and keeping the talent and entrepreneurs in the agriculture sector.Data from the Malaysian economy is used to illustrate this phenomenon of entrepreneurial drain from the rural sectors.